Affecting African American Men’s Prostate Cancer Screening Decision-making through a Mobile Tablet-Mediated Intervention - Sultan, Dawood H. (2014)
African American men experience a 60% higher incidence of prostate cancer and are more than twice as likely to die from it than White men. Evidence is insufficient to conclude that definitively screening for prostate cancer reduces the likelihood of morbidity or death. Patients are encouraged to discuss screening alternatives with health care providers for informed decision-making (IDM). The extent of IDM in clinical or community setting is not known. This study uses data from a community-based, computer-mediated, IDM intervention that targeted 152 African American aged 40 to 70. Pretest-posttest differences in means for prostate cancer knowledge, screening decisional conflict, and screening decisional self-efficacy were examined by two-tailed t-tests. Overall, the intervention significantly improved respondents’ prostate cancer knowledge (p<.0001), significantly improved decisional self-efficacy (p<.0001) and significantly reduced decisional conflict (p<.0001). Specifically, the intervention significantly promoted IDM among men who reported more education, being married, having financial resources, and younger age.